PEMANFAATAN SEL PUNCA PADA INFARK MIOKARD - Wangko, Loretta C.; Awaloei, J. H.; Pangemanan, Janry A. (UNIVERSITAS SAM RATULANGI, 2011)
Abstract: World-wide, myocardial infarction and heart failure are still the leading causes of deaths and use up a great deal of money. In myocardial infarction there frequently incur cardiomyocyte injuries. Naturally, resident cardiomyocytes will undergo proliferation and contribute to the increasing and repairing of myocardium post infarction. Unfortunately, this capacity of regeneration is very limited. Moreover, injured cardiomyocytes are replaced by scar tissues. Pharmacotherapy with ACE-Inhibitors and Î² blockers can give some clinical improvement, but can not inhibit the loss of cardiomyocytes. Nowadays, stem cell therapy has proclaimed some promising benefits. Among all the introduced stem cells, mesenchymal stem cells are the most popular since they have the capability to differentiate and then to develop into cardiomyocytes, maintain the myocardial thickness, reduce heart remodeling of the non infarct myocardium, improve heart function, and can be used from allogenic donors. Besides that, these cells are easier to obtain and isolate, are genetically stable, have the capacity for angiogenesis, homing to the injured areas or inflammation, and supplying growth factors and cytokines for tissue repair. Key words: stem cell, cardiomyocyte, transplantation, donor. Â Â Abstrak: Infark miokard dan gagal jantung masih merupakan penyebab kematian utama di dunia dan menyerap biaya pengobatan yang tinggi. Pada infark miokard sering terjadi cedera kardiomiosit. Secara alamiah kardiomiosit residen akan mengalami proliferasi dan mengambil bagian dalam meningkatkan dan memulihkan miokard pasca infark. Kapasitas regenerasi ini sangat terbatas. Selain itu kardiomiosit yang cedera akan digantikan oleh jaringan ikat. Farmakoterapi dengan penghambat ACE dan Î² bloker dapat memberikan perbaikan klinis, tetapi tidak dapat menghambat kehilangan kardiomiosit. Dewasa ini terapi sel punca telah mengumandangkan manfaat yang menjanjikan. Dari berbagai sel punca yang dikemukakan, sel punca mesensimal yang paling diminati oleh karena kemampuannya berdiferensiasi dan berkembang menjadi kardiomiosit, mempertahankan ketebalan miokard, menurunkan remodeling jantung pada bagian yang tidak infark, memperbaiki fungsi jantung. dan dapat diambil dari donor alogenik. Disamping itu, sel-sel ini lebih mudah diperoleh dan diisolasi, stabil secara genetik, berkapasitas angiogenesis, homing ke tempat cedera atau inflamasi, dan memasok growth factors dan sitokin untuk perbaikan jaringan. Kata kunci: sel punca, kardiomiosit, transplantasi, donor.